Homiletika Digital dalam Era Media Sosial: Analisis Tantangan dan Peluang Praktik Berkhotbah Kontemporer - Ayub Sugiharto; Indah Indah (Journal Of Spirituality And Practical Theology, 2026)
This article examines how preaching practices are evolving alongside the rapid expansion of social media. Rather than merely shifting platforms, preaching today is undergoing deeper changes in how messages are structured, communicated, and received by audiences. While many previous studies have focused on technological or communicative aspects, this paper attempts to bring those changes into a more integrated theological-homiletical reflection. Using a qualitative literature-based approach, this study identifies both the emerging challenges and the new opportunities within digital preaching practices. The findings indicate that adapting to digital media is not simply a matter of technical adjustment. It requires a rethinking of homiletical methods so that theological depth can be maintained while still engaging meaningfully with digital culture. This study, therefore, offers a more integrative perspective on preaching in the digital era.